Physical Activity as an Antidepressant for Psychiatric Hospital Patients - Mushoddiq Kalimatullah; Kuston Sultoni; Yati Rohayati; Jajat (Universitas Negeri Semarang, 2025)
Depression is a serious mental disorder that significantly impacts an individual's quality of life. Physical activity is considered a non-pharmacological program with the potential to alleviate depressive symptoms through biological, psychological, and social mechanisms. This study aims to evaluate the relationship between physical activity levels and depression levels among patients undergoing psychosocial rehabilitation at Marzoeki Mahdi Mental Hospital, Bogor. This research employs a quantitative design with a descriptive-correlational approach. A total of 26 patients diagnosed with major depressive disorder who actively participated in physical activity programs were purposively selected. The instruments used included the Hamilton Rating Scale for Depression (HRSD) and the Q-MOVE (Questionnaire of 24-Hour Movement Behaviors). The analysis results indicated no significant relationship between sleep duration or physical activity levels (sedentary, moderate, vigorous) and depression levels. However, a significant positive correlation was found between moderate and vigorous physical activity. This study concludes that although no direct relationship was found between physical activity and depression, an active behavior pattern still has the potential to support recovery. Further studies with a longitudinal design and larger sample sizes are needed to explore a more accurate causal relationship.